Akhlak yang Baik : Jujur dan Amanah Sebagai Pondasi Kehidupan yang Harmonis - Siti Sa’idah; Natasya Putri Salsabila; M. Mahbubi (Journal of Literature Review, 2025)
Good morals, honesty, and trustworthiness are three very important concepts in everyday life. Good morals include good and commendable behavior, honesty means telling the truth and not lying, while trustworthiness means being trustworthy and reliable. These three concepts are interrelated and can help individuals become better and more respected people. This study aims to determine how good morals, honesty, and trustworthiness can be the foundation of a harmonious life. By having good morals, individuals can build trust with others and improve their reputation. Honesty and trustworthiness can also help individuals become more trustworthy and reliable. The results of the study show that good morals, honesty, and trustworthiness can bring many benefits in everyday life. Individuals who have good morals, honesty, and trustworthiness can build harmonious relationships with others, increase their trust and reputation, and become better and more respected people. In conclusion, good morals, honesty, and trustworthiness are three very important concepts in everyday life. By having good morals, being honest and trustworthy, individuals can become better individuals and be more respected by others. Therefore, it is important for us to understand and practice good, honest and trustworthy morals in everyday life